Sistem Perbenihan Formal dan Informal Tanaman Pangan - Eman Paturohman; Sumarno Sumarno (Iptek Tanaman Pangan, 2017)
The food crop seed system had evolved in accordance with the progress of the farming development. In subsistence farming, seed supply is an integral part of the farming itself, whereby farmers obtain seed from the crops harvested in the previous season. Commercial intensive farming utilizes good seed quality of improved variety provided by commercial seed companies. When the seed is product and directly used by farmers, it is called an informal seed system, while seed which is produced according to the standard operation, including seed certification, it is called a formal seed system. Food crops production in Indonesia accomodates the informal seed system, especially for the farming on suboptimum lands and for legumes and tuber crops. Informal seed system provides seeds of many local adapted varieties, which are able to form the agrobiodiversities on the farm lands. Conversely, the formal seed system has provided certified seeds of improved varieties and hybrids, which have contributed significantly to the increases of national food production. Informal and formal seed systems both can go along harmoniously in providing seed for Indonesian farmers, because each has certain targeted farmers. Governmental seed program, therefore, should facilitate both the informal and formal seed system. Informal seed system of food crops should be more appreciated rather than being discouraged, because it is complementary to the formal seed system.